National Health Interview Survey, 2011 ([Verlag nicht ermittelbar], 2017)
The National Health Interview Survey (NHIS) is conducted annually and sponsored by the National Center for Health Statistics (NCHS), which is part of the U.S. Public Health Service. The purpose of the NHIS is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive across the United States population through the collection and analysis of data on a broad range of health topics. The redesigned NHIS questionnaire introduced in 1997 (see NATIONAL HEALTH INTERVIEW SURVEY, 1997 [ICPSR 2954]) consists of a Core that remains largely unchanged from year to year, plus an assortment of Supplements varying from year to year. The 2011 NHIS Core components contain Household, Family, Person, Sample Adult, and Sample Child files. Each record in Part 1, Household Level, contains data on type of living quarters, number of families in the household responding and not responding, and the month and year of the interview for each sampling unit. Part 2, Family Level, is made up of reconstructed variables from the person-level data of the basic module and includes information on sex, age, race, marital status, education, veteran status, family income, family size, major activities, health status, health care costs, activity limits, and employment status, along with industry and occupation. As part of the basic module, Part 3, Person Level, provides information on all family members with respect to health status, limitation of daily activities, cognitive impairment, and health conditions. Also included are variables related to doctor visits, hospital stays, and health care access and utilization. Basic demographic information is provided as well. A randomly-selected adult in each family was interviewed for Part 4, Sample Adult Level, regarding respiratory conditions, renal conditions, AIDS, joint symptoms, health status, health care and doctor visits, limitation of daily activities, and behaviors such as smoking, alcohol consumption, and physical activity. Part 5, Sample Child Level, provides information from an adult in the household on medical conditions of one child in the household, such as developmental or intellectual disabilities, respiratory problems, seizures, allergies, and use of special equipment like hearing aids, braces, or wheelchairs. Parts 6 through 11 comprise the additional Supplements and Paradata for the 2011 NHIS. Part 6, Injury/Poison Episode, is an episode-based file that contains information about the external cause and nature of the injury or poisoning episode and what the person was doing at the time of the injury or poisoning episode, in addition to the date and place of occurrence. Part 7, Adult Disability Level and Part 8, Child Disability Level, are a supplemental set of six questions asked at the end of the Sample Adult and Sample Child Questionnaires for half of families that did not receive the Family Disability Supplement. These specific disability questions were only asked of the Sample Adult and the Sample Child. Part 9, Family Disability Level, seeks to identify the subpopulation that is at a greater risk than the general population of experiencing restrictions in social participation, for example, restrictions in employment, education, or civic life. Specific questions ask about respondent difficulty performing daily activities, such as dressing, bathing, or walking. Approximately one half of sample adults were selected to receive the Part 10, Adult Functioning and Disability Level Supplement. Questions were asked about a respondent's functioning in various basic and complex activity domains: vision, hearing, mobility, communication, cognition, upper body, affect, pain, and fatigue. This supplement also included questions designed to capture an individual's ability to participate in society. Follow-up questions on the degree of difficulty, use of assistive devices, and functioning with assistance were included for most domains. Part 11, Paradata Level, does not contain health related information, but rather data which are related to the interview process, including measures of time, contact-ability, and cooperation. Please see the User Guide for additional information and details.